2023
DOI: 10.1029/2023ja031703
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of a Few Problems in the Application of Quasilinear Theory to Calculating Diffusion Coefficients in Heliophysics

Gregory S. Cunningham

Abstract: A theory of quasilinear diffusion for obliquely propagating electromagnetic waves was developed in the 1960’s and applied in the 1970’s to model scattering of relativistic electrons by a prescribed distribution of waves. In the latter work, a transformation of variables, from wavevector space to the temporal frequency and tangent of the wave normal angle, was used so that simple Gaussian functions of frequency and tangent of the wave normal angle could be multiplied together to define the distribution of wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(285 reference statements)
0
3
0
Order By: Relevance
“…While the Cunningham result merits further study, it has yet to be demonstrated that the differences are significant once the diffusion coefficients have been bounce-and driftaveraged and the different wave modes combined. For the reasons above, it is unlikely that the differences demonstrated in Cunningham (2023) would substantially alter the results presented here, but this does need to be tested thoroughly elsewhere.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…While the Cunningham result merits further study, it has yet to be demonstrated that the differences are significant once the diffusion coefficients have been bounce-and driftaveraged and the different wave modes combined. For the reasons above, it is unlikely that the differences demonstrated in Cunningham (2023) would substantially alter the results presented here, but this does need to be tested thoroughly elsewhere.…”
Section: Discussionmentioning
confidence: 95%
“…These effects can be investigated using 2-and 3dimensional radiation belt models and this will be the subject of further work. Cunningham (2023) suggests that, in certain situations, some of the assumptions underlying the calculation of diffusion coefficients by the PADIE code and similar codes may be improved. At low values of the ratio of the plasma frequency to the gyro frequency, f pe /f ce = 1.5, and at wave-normal angles very close to the resonance cone this can lead to significant differences in the local diffusion coefficients at some energies and pitch angles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation